Evidence That Romanian Entrepreneurs Are Opportunity-Driven, Rather Than Necessity-Driven: A Macroeconomic Spatial Analysis - Horia TIGAU; Mihai ANTONIA (Communications of International Proceedings, 2020)
The purpose of our study is to investigate the macroeconomic factors influencing new firm formation in Romania, using a spatial panel framework. Entrepreneurship and macroeconomic factors influence each other in various ways, as there are many determinants of regional entrepreneurship dynamics in contemporary Romania. The main hypothesis of this paper tries to indicate whether the Romanian Entrepreneur is opportunity-driven or necessity-driven. Several other papers have shown that the entrepreneurial attitude differs by country, due to the business framework or to cultural aspects. The other tested hypothesis is whether there exist spatial spillover effects between Romanian counties with respect to the ratio of new businesses to active business population. The paper develops a holistic conceptualization of the spatial variation of start-ups in Romania and empirically investigates determinants of the birth of new firms, using data over the period 2008-2018 at the NUTS 3 level. The results suggest that the unemployment rate, the resource utilization rate and the number of active firms per thousand inhabitants have a significant influence on the proportion of newly created firms in the total number of active firms. Returning to the hypotheses, the authors conclude that Romanian entrepreneurs in the aforementioned period have been more opportunity-driven, while spatial spillover effects have shown to be significant.
Keywords: Entrepreneurship; Unemployment Rate; Spatial Panel; Macroeconomic Factors.